Design, Assembly and Test of G-CLEF\'s Exposure Meter - Volpato, Henrique Lupinari (2024)
This project aims to develop a versatile, high-efficiency, low-resolution spectrograph designed as the exposure meter for G-CLEF (GMT-Consortium Large Earth Finder). G-CLEF is a cutting-edge, high-resolution echelle spectrograph slated to be the first-generation instrument for the Giant Magellan Telescope (GMT), scheduled for completion in time for the telescopes first light. The exposure meter is crucial for adjusting Barycentric Corrections (BC) in Doppler radial velocity (RV) measurements, accounting specifically for Earths chromatic atmospheric effects. This correction is particularly significant in Extreme Precision RV (EPRV) measurements since atmospheric wavelength dependencies can introduce errors at scales as fine as tens of centimeters per second, which is the same level of precision required for detecting Earth-like planets orbiting Sun-like stars, a primary scientific goal of G-CLEF. This work delves into the detailed scientific rationale, presents the design trade-offs and performance simulations to achieve a precision of 1 cm/s in EPRV measurements, and outlines the key parameters derived from these analyses. It also discusses the optical and mechanical designs grounded in validated requirements identified through performance simulations. Additionally, it covers the assembly and testing phase of the exposure meter prototype, along with the results that confirm the effectiveness of the design.